ARABIC DISCUSSION FORUM AS A MEDIUM FOR DEVELOPING COMMUNICATIVE COMPETENCE AMONG SANTRIWATI AT PONDOK MODERN DARUSSALAM GONTOR PUTRI 1 - Fairuz Subakir; Siti Nikmatul Rochma; Nuraeni Rahmawati; Nur Fera Khalifah (STKIP Pesisir Selatan, 2026)
This study investigates the role of the Arabic Discussion Forum as a medium for developing communicative competence among santriwati at Pondok Modern Darussalam Gontor Putri 1. Employing a qualitative case study design, the research explores how discussion-based activities contribute to students' Arabic communicative development within the pesantren language environment. Data were collected through participant observation, semi-structured interviews, and document analysis involving santriwati, language supervisors, and dormitory coordinators. The findings reveal that the Arabic Discussion Forum significantly contributes to the development of linguistic, sociolinguistic, discourse, and strategic competence. The forum provides authentic communicative situations that encourage students to negotiate meaning, express opinions, organize arguments, and interact spontaneously in Arabic. Furthermore, the forum enhances students' confidence, reduces speaking anxiety, and strengthens willingness to communicate actively. The effectiveness of the forum is strongly supported by the pesantren's Arabic-speaking environment, which integrates formal instruction with daily communicative interaction.